Strategi bank syariah dalam meningkatkan awareness dan kepercayaan masyarakat indonesia terhadap produk keuangan syariah - A'yun, Najwa Qurrota (Maliki Interdisciplinary Journal, 2025)
This study aims to determine strategies that can be used by Islamic banks to increase brand awareness and public trust in Islamic banking products and services in Indonesia. Although the growth of Islamic banks has proven very rapid, the target market and users of Islamic banks are still relatively low compared to conventional banks. Lack of public knowledge and trust are the main factors that make Islamic banks less attractive. This problem can be overcome through communication strategies, public education, and service digitization. This writing uses a qualitative descriptive approach with a literature study method from several journals, including research by (Putri & Rahayu, 2024), (Anandia & Aisyah, 2023), and (Febrian & Budianto, 2023) from UIN Maulana Malik Ibrahim Malang. The results of this analysis indicate that public trust can be influenced by the security of bank services, information transparency, service quality, and consistency of Islamic values in Islamic bank operations. In addition, increasing brand awareness can be achieved through branding strategies, Islamic financial literacy, and the use of digital media, which is currently developing rapidly. The combination of digital technology, public education, and transparent communication can build a positive image of Islamic banks, which can then attract and expand the customer base of Islamic banks in Indonesia.